2013
DOI: 10.2903/j.efsa.2013.3313
|View full text |Cite
|
Sign up to set email alerts
|

International Frameworks Dealing with Human Risk Assessment of Combined Exposure to Multiple Chemicals

Abstract: The development of harmonised terminology and frameworks for the human risk assessment of combined exposure to multiple chemicals ("chemical mixtures") is an important area for EFSA and a number of activities have already been undertaken, i.e. in the fields of pesticides and contaminants. The first step prior to a risk assessment of combined exposure to multiple chemicals is problem formulation defining the relevant exposure, hazard and population to be considered. In practice, risk assessment of multiple chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(24 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The original data on combined toxic effects of mycotoxins are limited and therefore the health risk from this multi-exposure is not well-known [97]. Risk assessment of combined exposure to multiple chemicals is defined as a priority objective by European Food Safety Authority (EFSA) and EU [98]. Among the 116 reported possible mycotoxins combinations found by the different authors in cereals and derived cereal product samples, AFs + FUMs, DON + ZEN, AFs + OTA and FUMs + ZEN were the most present ones [99].…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 99%
“…The original data on combined toxic effects of mycotoxins are limited and therefore the health risk from this multi-exposure is not well-known [97]. Risk assessment of combined exposure to multiple chemicals is defined as a priority objective by European Food Safety Authority (EFSA) and EU [98]. Among the 116 reported possible mycotoxins combinations found by the different authors in cereals and derived cereal product samples, AFs + FUMs, DON + ZEN, AFs + OTA and FUMs + ZEN were the most present ones [99].…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 99%
“…Data from monitoring systems focused on pesticides and other chemicals in food will in the future also be used for risk assessment of combined exposure to multiple chemicals ("chemical mixtures"). Typically, risk assessment of multiple chemicals is conducted using a tiered approach for exposure assessment, hazard assessment and risk characterization [18], an approach that clearly needs update as new data from animal experiments show the potential for additive effect of such chemicals [19].…”
Section: The Future Of One Health Food Safetymentioning
confidence: 99%
“…Experiments have shown that chemicals, when exerting similar effects, typically act in a dose-additive manner, and far less frequently in synergistic or antagonistic ways [3,4]. This means that the efficacies of chemicals in a mixture can be added together, as long as the potency of the individual chemicals is appropriately accounted for.…”
Section: Additive Mixture Effectsmentioning
confidence: 99%